2023
DOI: 10.1038/s41587-023-01934-1
|View full text |Cite
|
Sign up to set email alerts
|

Multi-omics data integration using ratio-based quantitative profiling with Quartet reference materials

Yuanting Zheng,
Yaqing Liu,
Jingcheng Yang
et al.

Abstract: Characterization and integration of the genome, epigenome, transcriptome, proteome and metabolome of different datasets is difficult owing to a lack of ground truth. Here we develop and characterize suites of publicly available multi-omics reference materials of matched DNA, RNA, protein and metabolites derived from immortalized cell lines from a family quartet of parents and monozygotic twin daughters. These references provide built-in truth defined by relationships among the family members and the informatio… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
3
1

Relationship

3
5

Authors

Journals

citations
Cited by 24 publications
(10 citation statements)
references
References 109 publications
0
9
1
Order By: Relevance
“…The SV was associated with standing height in our cohort, individuals carrying this SV displayed a lower standing height (median height = 164 cm) than that of the noncarriers (median height = 165 cm), consistent with the reduced body length caused by knocking out of the Wwp2 gene in mice 74,75 . While the difference was not statistically significant due to the relatively small sample size (n = 1,016) in the present study ( P value = 0.28, one- way ANOVA ), we found that the SV is in complete linkage disequilibrium with rs8052428-T, which is ∼55 kb downstream to the SV, based on manual examination of the Pacbio HiFi data from a Chinese quartet family (http://chinese-quartet.org/) 76 . rs8052428-T is significantly associated with shorter sitting height ( Beta = -0.101, P value = 1.1E-29 ) and standing height ( Beta = -0.132, P value = 1.0E-17 ) in a prior genome-wide association study (GWAS) of height variation of 361,194 UK Biobank samples (http://www.nealelab.is/uk-biobank/).…”
Section: Maincontrasting
confidence: 82%
“…The SV was associated with standing height in our cohort, individuals carrying this SV displayed a lower standing height (median height = 164 cm) than that of the noncarriers (median height = 165 cm), consistent with the reduced body length caused by knocking out of the Wwp2 gene in mice 74,75 . While the difference was not statistically significant due to the relatively small sample size (n = 1,016) in the present study ( P value = 0.28, one- way ANOVA ), we found that the SV is in complete linkage disequilibrium with rs8052428-T, which is ∼55 kb downstream to the SV, based on manual examination of the Pacbio HiFi data from a Chinese quartet family (http://chinese-quartet.org/) 76 . rs8052428-T is significantly associated with shorter sitting height ( Beta = -0.101, P value = 1.1E-29 ) and standing height ( Beta = -0.132, P value = 1.0E-17 ) in a prior genome-wide association study (GWAS) of height variation of 361,194 UK Biobank samples (http://www.nealelab.is/uk-biobank/).…”
Section: Maincontrasting
confidence: 82%
“…In a PT effort aimed to assess the quality of the omics technology platforms of EATRIS-Plus partners, the EATRIS-Plus project acquired Quartet multi-omics reference materials from Fudan University (Shanghai, China). The Quartet reference materials encompass DNA, RNA, protein, and metabolites, all derived from B-lymphoblastoid cell lines obtained from a familial quartet consisting of parents and monozygotic twin daughters (21)(22)(23)(24). The Quartet Project is a pivotal resource, providing "multi-omics ground truth", best practices, and computational methods for objective assessment of proficiency and reliability of data generation processes in participating laboratories (Figure 3) The Chinese Quartet reference materials and the quality assessment system.…”
Section: Research Omics Reference Material: the Fudan Quartet Projectmentioning
confidence: 99%
“…For qualitative omics, the F1-score is a commonly used measure that takes into account both false positives and false negatives by computing a harmonic mean of precision and recall. Quality metrics for assessing reliability of DNA-seq, RNA-seq, proteomics, and metabolomics in terms of intra-batch proficiency and cross-batch reproducibility are assessed using ratio-based reference datasets (23). The Pearson correlation coefficient between the ratio-based expression levels of test datasets and reference datasets are used to describe the accuracy of quantitation.…”
Section: Proficiency Testing Of Eatris Plus Facilitiesmentioning
confidence: 99%
See 1 more Smart Citation
“…Recently, the Quartet project for quality control and data integration of multi-omics profiling, introduced multi-omics reference materials derived from immortalized B-lymphoblastoid cell lines from a Chinese quartet family of parents and monozygotic twin daughters, and developed ratio-based reference datasets 24 . These well-characterized, homogenous, and stable Quartet RNA reference materials with small inter-sample biological differences, provided a unique opportunity for the assessment and benchmarking of transcriptome profiling at subtle differential expression levels in a reference-based manner 23 .…”
Section: Introductionmentioning
confidence: 99%